A Comparison of Classification Algorithms for Predicting Distinctive Characteristics in Fine Aroma Cocoa Flowers Using WEKA Modeler - Tineo Flores, Daniel; Murillo, Yuriko S.; Marin, Mercedes; Gomez Fernandez, Darwin; Taboada, Víctor H.; Goñas Goñas, Malluri; Quiñonez Huatangari, Lenin (IQ, 2025)
Author contribution: All authors made an equal contribution to the development and planning of the study. Conflict of Interest: The authors have no potential conflicts of interest, or such divergences linked with this research study. Data Availability Statement: Data are available from the authors upon request.